US patent no. 6,754,594 B2: Digital flowmeter - Henry, M; Clarke, D; Vignos, J (United States Patent and Trademark Office, 2004)
A digital flowmeter includes a vibratable conduit, a driver connected to the conduit and operable to impart motion to the conduit, and a sensor connected to the conduit and operable to sense the motion of the conduit. A control and measurement system is connected to the driver and the sensor. The control and measurement system includes circuitry to receive a sensor signal from the sensor, generate a drive signal based on the sensor signal using digital signal processing, supply the drive signal to the driver, and generate a measurement of a property of a two-phase material flowing through the conduit based on the signal from the sensor.